Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài

Những câu hỏi liên quan
gh
Xem chi tiết
Khánh Ngọc
30 tháng 10 2020 lúc 20:54

1. \(VT=\sqrt{7+4\sqrt{3}}-\sqrt{7-4\sqrt{3}}\)

\(=\sqrt{2^2+2.2.\sqrt{3}+\left(\sqrt{3}\right)^2}-\sqrt{2^2-2.2.\sqrt{3}+\left(\sqrt{3}\right)^2}\)

\(=\sqrt{\left(2+\sqrt{3}\right)^2}-\sqrt{\left(2-\sqrt{3}\right)^2}\)

\(=2+\sqrt{3}-2+\sqrt{3}=VP\)

Khách vãng lai đã xóa
l҉o҉n҉g҉ d҉z҉
30 tháng 10 2020 lúc 20:55

Bài 1.

Ta có : \(\sqrt{7+4\sqrt{3}}-\sqrt{7-4\sqrt{3}}\)

\(=\sqrt{3+4\sqrt{3}+4}-\sqrt{3-4\sqrt{3}+4}\)

\(=\sqrt{\left(\sqrt{3}+2\right)^2}-\sqrt{\left(\sqrt{3}-2\right)^2}\)

\(=\left|\sqrt{3}+2\right|-\left|\sqrt{3}-2\right|\)

\(=\sqrt{3}+2-\left(2-\sqrt{3}\right)\)

\(=\sqrt{3}+2-2+\sqrt{3}=2\sqrt{3}\left(đpcm\right)\)

Khách vãng lai đã xóa
l҉o҉n҉g҉ d҉z҉
30 tháng 10 2020 lúc 21:04

Bài 2.

\(P=\left(\frac{1}{x-\sqrt{x}}+\frac{\sqrt{x}}{\sqrt{x}-1}\right)\div\left(\frac{2}{x-1}+\frac{1}{\sqrt{x}+1}\right)\)

ĐKXĐ : \(\hept{\begin{cases}x>0\\x\ne1\end{cases}}\)

\(=\left(\frac{1}{\sqrt{x}\left(\sqrt{x}-1\right)}+\frac{x}{\sqrt{x}\left(\sqrt{x}-1\right)}\right)\div\left(\frac{2}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}+\frac{\sqrt{x}-1}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}\right)\)

\(=\frac{x+1}{\sqrt{x}\left(\sqrt{x}-1\right)}\div\frac{\sqrt{x}+1}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}\)

\(=\frac{x+1}{\sqrt{x}\left(\sqrt{x}-1\right)}\times\frac{\sqrt{x}-1}{1}=\frac{x+1}{\sqrt{x}}\)

Xét P - 2 ta có :

\(P-2=\frac{x+1}{\sqrt{x}}-2=\frac{x+1}{\sqrt{x}}-\frac{2\sqrt{x}}{\sqrt{x}}=\frac{x-2\sqrt{x}+1}{\sqrt{x}}=\frac{\left(\sqrt{x}-1\right)^2}{\sqrt{x}}\)

Với \(\hept{\begin{cases}x>0\\x\ne1\end{cases}}\Rightarrow\hept{\begin{cases}\left(\sqrt{x}-1\right)^2>0\\\sqrt{x}>0\end{cases}}\Rightarrow\frac{\left(\sqrt{x}-1\right)^2}{\sqrt{x}}>0\)

=> \(P-2>0\)

=> \(P>2\)

Khách vãng lai đã xóa
Thư Nguyễn
Xem chi tiết
mạnh Vũ đức
Xem chi tiết
Nguyễn Thị Thanh Tâm
Xem chi tiết
Nguyễn Đức  Minh
23 tháng 5 2021 lúc 12:36

\(\frac{4+\sqrt{X}}{7}\)

Khách vãng lai đã xóa
Lê Thụy Sĩ
Xem chi tiết
Nguyễn Tất Đạt
23 tháng 7 2018 lúc 19:10

\(B=\left(\frac{1}{\sqrt{x}\left(\sqrt{x}+1\right)}-\frac{1}{\sqrt{x}+1}\right).\frac{\left(\sqrt{x}+1\right)^2}{\sqrt{x}-1}\)

\(B=\frac{1-\sqrt{x}}{\sqrt{x}\left(\sqrt{x}+1\right)}.\frac{\left(\sqrt{x}+1\right)^2}{\sqrt{x}-1}\)

\(B=\frac{-\sqrt{x}-1}{\sqrt{x}}\). Vậy ....

Kha Nguyễn
Xem chi tiết
Ngô Chi Lan
29 tháng 8 2020 lúc 14:40

Bài làm:

Ta có: 

\(P=\left(1-\frac{x-3\sqrt{x}}{x-9}\right)\div\left(\frac{\sqrt{x}-9}{2-\sqrt{x}}+\frac{\sqrt{x}-2}{3+\sqrt{x}}-\frac{9-x}{x+\sqrt{x}-6}\right)\)

\(P=\frac{x-9-x+3\sqrt{x}}{\left(\sqrt{x}-3\right)\left(\sqrt{x}+3\right)}\div\left[\frac{\left(9-\sqrt{x}\right)\left(3+\sqrt{x}\right)+\left(\sqrt{x}-2\right)^2-9+x}{\left(\sqrt{x}-2\right)\left(\sqrt{x}+3\right)}\right]\)

\(P=\frac{3\sqrt{x}-9}{\left(\sqrt{x}-3\right)\left(\sqrt{x}+3\right)}\div\frac{-x+6\sqrt{x}+27+x-4\sqrt{x}+2-9+x}{\left(\sqrt{x}-2\right)\left(\sqrt{x}+3\right)}\)

\(P=\frac{3}{\sqrt{x}+3}\div\frac{x+2\sqrt{x}+20}{\left(\sqrt{x}-2\right)\left(\sqrt{x}+3\right)}\)

\(P=\frac{3}{\sqrt{x}+3}\cdot\frac{\left(\sqrt{x}-2\right)\left(\sqrt{x}+3\right)}{x+2\sqrt{x}+20}\)

\(P=\frac{3\left(\sqrt{x}-2\right)}{x+2\sqrt{x}+20}=\frac{3\sqrt{x}-6}{x+2\sqrt{x}+20}\)

Khách vãng lai đã xóa
Nguyễn Diệu Linh
Xem chi tiết
Hai Van
Xem chi tiết
Đoàn Đức Hà
9 tháng 10 2021 lúc 0:34

\(A=\left(\frac{1}{x-\sqrt{x}}\right)\div\frac{\sqrt{x}+1}{x-2\sqrt{x}+1}\)

\(=\frac{1}{\sqrt{x}\left(\sqrt{x}-1\right)}.\frac{x-2\sqrt{x}+1}{\sqrt{x}+1}\)

\(=\frac{\left(\sqrt{x}-1\right)^2}{\sqrt{x}\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}\)

\(=\frac{\sqrt{x}-1}{x+\sqrt{x}}\)

Tại \(x=4+2\sqrt{3}\)\(\sqrt{x}=\sqrt{4+2\sqrt{3}}=\sqrt{\left(\sqrt{3}+1\right)^2}=\sqrt{3}+1\)

\(A=\frac{\sqrt{3}}{4+2\sqrt{3}+\sqrt{3}+1}=\frac{\sqrt{3}}{5+3\sqrt{3}}\)

\(A-1=\frac{\sqrt{x}-1}{x+\sqrt{x}}-1=\frac{-1-x}{x+\sqrt{x}}< 0\)do \(x>0\).

Vậy \(A< 1\).

Khách vãng lai đã xóa
Phạm Minh Thành
Xem chi tiết